Assessing and improving student organizations : student workbook - Nolfi, Tricia (Stylus Pub., 2010)
Intended to be used in tandem with the Guide for Students. Each page presents an action or reflection slide from the Guide with a space below for participants to note their own ideas, outcomes of discussions, and items for action. It becomes a record of assessment sessions, and a resource to refer back to during implementation.